ENVIRONMENTAL ASSESSMENT OF SOLID WASTE IN THE LEFT SIDE OF MOSUL CITY - Abdulkareem Nadhim Mohammed Alzuhairy; Mazin Nazar Fadhel (Scholar Express Journal, 2022)
The study included all areas of the left side of the city of Mosul, and in each area or residential neighborhood, two sites were randomly selected, where samples are collected on a daily basis after distributing the bags to the specified sites, for a period of six months. Where the results of the research conducted in the year 2021-2022 showed that the left side of the city of Mosul produces approximately (780) tons per day of municipal solid waste, Where the results of the study showed through the field survey process that the study area contains more than 397 landfills for waste within residential neighborhoods, which occupy an area of more than 28376m2 . As organic waste constitutes the largest proportion of the components, with a percentage (67.50%), plastic, nylon (7.66%), paper and cardboard (10.32%), glass (3.10%), metals (1.02%), textiles (2.99%), wood (1.65%), diapers ( 5.74%), so some of them must be recycled and others re-used and treated to produce other materials, thus reducing the volume of waste and producing other materials such as organic fertilizers and soil conditioners, and in the end we reduce the use of land as landfill sites, as well as providing an economic resource for the city and the country in general.
Keywords: Solid waste; Mosul city; Production rate; Random landfills